(untitled) (Bangladesh Journal of Zoology, 2015)
A total of 1570 adolescent girls (aged 10-19 years) of rural, urban and slum areas in and around Dhaka city were investigated to determine the association of anaemia with parasitic infection. About one third (33.50%) of the adolescent girls were found to be infected with one or more protozoans (Entamoeba histolytica, Giardia lamblia) and helminths (Ascaris lumbricoides, Trichuris trichura, Strongyloieds stercoralis, hookworms). Anaemia (32.22%) was reported among the adolescent girls and 39.52% anaemic girls were infected with intestinal parasites against the 30.63% non anaemic cases. Anaemia was significantly associated with parasitic infestation (?2 =11.76, p<0.000). Percentage of anaemic cases was higher in slum area (38.75%) and lower in urban area (24.11%) respectively. Socioeconomic status of the adolescent girls had also impact on the prevalence of parasites and anaemia. Parasitic infestation was much lower (16.10%) among the literate compared to the illiterate respondents (47.58%). The prevalence of parasite infection was positively associated with illiterate adolescent girls (?2=171.27, OR=4.73, p<0.000). The level of education was inversely related (r = -0.98, p<0.01) with the prevalence of anaemia. Unhygienic latrine users were associated with parasite infection (OR=2.80) and anaemia (OR=2.16) respectively. The present study revealed that parasitic infection and socioeconomic status may be responsible for anaemia among the adolescent girls. Bangladesh J. Zool. 42(1): 91-103, 2014